Sustainable development practices in MICE (meeting, incentives, convention & exhibition) tourism / Maisarah Abdul Hamid...[et al.] - Abdul Hamid, Maisarah; Awang, Khairil Wahidin; Ismail, Noralisa; Mohamad Fuza, Zatul Iffah; Ahmad, Khairun Najiah (2014)
MICE ( meeting, incentives, convention& exhibition) tourism is a growing sectors in Malaysia. Undeniably it able to attract tourist to come to Malaysia and do their business here. Realizing the importance of this sector, it is necessary to prepare a guidelines for the industry so that it able to sustain for a long time. Malaysia nowadays is promoting tourism and at the same time applying the sustainable development concept. So, this study will be conducted to see the practices that suitable for the industry to apply sustainable development and at the same time promoting MICE tourism to the world. The study will focus from Malaysia perspectives. The samples of the study will be the buyers and the suppliers of MICE industry in Malaysia. The buyers will response on the human systems dimensions while the suppliers will respond on ecosystem dimension. Interviews will be conducted with the focus group(the suppliers) to look at the practices that used in the MICE venues. Then, structured questionnaire consist of open ended and close ended questions will be prepared and distributed to the suppliers and buyers of the industry. The expected outcome will showed the suitable practices that can be applied for MICE tourism and at the same time, the awareness about the sustainable development concept can be revealed especially from the buyers and suppliers perspectives.